Space in ancient Greek literature : studies in ancient Greek narrative - Jong, Irene J. F. de (Mnemosyne, bibliotheca classica Batava. Supplementum, 2012)
The third volume of the Studies in Ancient Greek narrative deals with the narratological category of space: how is space, including objects which function as 'props', presented in narrative texts and what are its functions (thematic, symbolic, psychologising, or characterising).